Controlling T cell–tumor cell interaction with a biomimetic physical barrier for cancer immunotherapy - Yuxuan Zhang; Jinjin Wang; Guangchao Qing; Yongchao Wang; Xianlei Li; Ting Luo; Yi-Feng Wang; Lu Liu; Yufei Wang; Qiankun Ni; Shuyi Li; Junge Chen; et al. (Proceedings of the National Academy of Sciences, 2025)
Cancer immunotherapy has shown tremendous promise in various cancers. However, current strategies, such as immune checkpoint blockade, primarily restore exhausted T cells but provide only transient efficacy, as the rapid clearance of antibodies. Their limited durability is further hindered by persistent T cell-tumor cell interactions that accelerate T cell exhaustion. To prevent T cells from sustained exposure to these interactions, we present a hydrogel-based biomimetic physical barrier (BPB) here to create a “protective zone” for T cells. The BPB temporarily blocks T cell-tumor cell interactions and shields T cells from inactivation and exhaustion, allowing them to accumulate and maintain their functional activity in the tumor microenvironment. After sufficient T cell accumulation, the dismantling of BPB triggered by near-infrared light irradiation-induced gel-sol transition will restore the interaction between T cells and tumor cells. This controlled re-exposure allows the accumulated T cells to attack the tumor cells in a more activated and anti-exhaustion state, maximizing their tumor-killing potential. Moreover, BPB not only enhances immediate tumor regression but also triggers systemic immune activation and durable memory responses, enabling long-term protection against tumor rechallenge and effective control of multifocal tumors. Collectively, our BPB for modulating the T cell-tumor cell interaction has great prospects for advancing cancer immunotherapy.